Energy analysis of a novel solar tri-generation system using different ORC working fluids. (May 2023) - Almohammadi, Bandar Awadh; Al-Zahrani, Ahmed; Refaey, H.A.; Attia, El-Awady; Fouda, A.
Abstract: A novel solar tri-generation system combined with an Organic Rankin Cycle (ORC), humidification dehumidification water desalination system (HDH), and a desiccant cooling system (DCS) for electrical power generation, water desalination, and air-conditioning is investigated numerically. Such a system is intended for tiny and medium-sized structures in Gulf nations that are abundant in solar energy but deficient in fossil fuels and water supplies. Detailed parametric studies of the operating and design parameters on the system's productivities and performance are carried out using different kinds of organic fluids (n-Octane, R245fa, R113, R123, Cyclohexane, and Toluene). It is noticed that the proposed system can provide the highest electrical power, fresh water, and space cooling capacity of 152.5 kW, 77.29 kg/s kg/h, and 27.11 kW, respectively, using Cyclohexane. Moreover, the maximum energy utilization factor obtained is 0.3018 using R123 and the improvement percentage of using R123 instead of n-Octane is 20%. Finally, general numerical correlations of a system's productivities and its performance are developed and presented within reasonable errors for different organic fluids. Graphical abstract: Image 1